Konsep Wara’ Menurut Pandangan Syaikh Az-Zarnuji dalam Kitab Ta’lim al-Muta’allim - Al Hamid, Ahmad (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2023)
This research aims to determine the concept of wara’ according to the views of Shaikh Az-Zarnuji in the book Ta'limul Muta'allim and the relevance of this concept according to the extension of Shaikh Az-Zarnuji in the book Ta'limul Muta'allim. Using a qualitative descriptive approach as a research method and collecting data using library research. Based on research conducted, it is known that according to Shaykh Az-Zarnuji's view, wara’ is defined as protecting oneself from the limits of religious norms, from everything that is not useful according to religion. This wara’ attitude needs to be implemented by students of science.